Original papersHerpes simplex virus infection – survey on knowledge of herpes virus infection among people aged 18–35 - Biało-Wójcicka, Ewelina; Majewski, Sławomir; Łoza, Katarzyna (Dermatology Review/Przegląd Dermatologiczny, 2015)
Introduction . Genital herpes is one of the most common sexually transmitted viral diseases and the most common cause of mucous membrane ulcerations in the genital area. The number of sexually transmitted infections caused by herpes virus (HSV), especially by HSV-1, is increasing. In the Polish population, there are no precise and current epidemiological data on herpes virus infections, especially in the anogenital area. A major problem concerns HSV infections in pregnancy, which are connected with the risk of in-utero and perinatal virus transmission. Herpes simplex virus infection in pregnancy threatens the life and health of an infant. Objective . To obtain information regarding the occurrence of herpes simplex in people of reproductive age as well as the assessment of knowledge on HSV infection and transmission, especially in pregnancy. Material and methods. Two hundred people (133 women and 67 men) aged 18–35 years, attending a dermatological clinic in the first half of 2014 with typical dermatological diseases, took part in the study. The subjects filled in the questionnaire including information on age, occurrence of erosions, scabs in the facial and genital area, diagnosis of oral and genital herpes virus infection, information given by the medical staff on the herpes infection, treatment with oral antivirus drugs, danger of herpes infection in pregnancy and risk of transmission of the HSV virus to fetuses and newborns. Results . Among the 200 people who took part in the study, 27% indicated the occurrence of herpes or recurring lesions in the form of vesicles and scabs on the border of skin and mucous membranes; in 1.5% of them genital herpes was diagnosed. Only 12% of investigated persons were treated with antiviral medicines. Sixty-eight percent of subjects stated that HSV is an infectious disease, 16% claimed that it is non-infectious, and a similar number did not know if it is an infectious disease or not. Only half of the studied group answered that it is dangerous for pregnant women and newborns, and 86% had never received sufficient information on herpes virus infection from medical staff. Conclusions . Our results confirm the lack of sufficient knowledge on HSV infection, especially in pregnancy, and the necessity of educating patients.